Ionizing radiation, inflammation, and their interactions in colon carcinogenesis in Mlh1‐deficient mice. Issue 3 (12th February 2015) - Morioka, Takamitsu; Miyoshi‐Imamura, Tomoko; Blyth, Benjamin J.; Kaminishi, Mutsumi; Kokubo, Toshiaki; Nishimura, Mayumi; Kito, Seiji; Tokairin, Yutaka; Tani, Shusuke; Murakami‐Murofushi, Kimiko; Yoshimi, Naoki; Shimada, Yoshiya; et al.
Abstract : Genetic, physiological and environmental factors are implicated in colorectal carcinogenesis. Mutations in the mutL homolog 1 ( MLH1 ) gene, one of the DNA mismatch repair genes, are a main cause of hereditary colon cancer syndromes such as Lynch syndrome. Long‐term chronic inflammation is also a key risk factor, responsible for colitis‐associated colorectal cancer; radiation exposure is also known to increase colorectal cancer risk. Here, we studied the effects of radiation exposure on inflammation‐induced colon carcinogenesis in DNA mismatch repair‐proficient and repair‐deficient mice. Male and female Mlh1 −/− and Mlh1 +/+ mice were irradiated with 2 Gy X‐rays when aged 2 weeks or 7 weeks and/or were treated with 1% dextran sodium sulfate (DSS) in drinking water for 7 days at 10 weeks old to induce mild inflammatory colitis. No colon tumors developed after X‐rays and/or DSS treatment in Mlh1 +/+ mice. Colon tumors developed after DSS treatment alone in Mlh1 −/− mice, and exposure to radiation prior to DSS treatment increased the number of tumors. Histologically, colon tumors in the mice resembled the subtype of well‐to‐moderately differentiated adenocarcinomas with tumor‐infiltrating lymphocytes of human Lynch syndrome. Immunohistochemistry revealed that expression of both p53 and β‐catenin and loss of p21 and adenomatosis polyposis coli proteins were observed at the later stages of carcinogenesis, suggesting a course of molecular pathogenesis distinct from typical sporadic or colitis‐associated colon cancer in humans. In conclusion, radiation exposure could further increase the risk of colorectal carcinogenesis induced by inflammation under the conditions of Mlh1 deficiency. Abstract : In this study, we examined the effect of X‐rays in combination with dextran sodium sulfate (DSS)‐induced inflammatory colitis on colon carcinogenesis in C57BL/6 Mlh1 +/+ and Mlh1 −/− mice. No colon tumors were observed in Mlh1 +/+ mice with any treatment. Colon lesions developed after DSS alone, or in combination with X‐rays in Mlh1 −/− mice. Incidence and multiplicity of colon lesions were generally higher when DSS treatment was combined with X‐ray exposure, particularly in male Mlh1 −/− mice.